The perception of nurses in high risk wards regarding the cost-effectiveness and practicality of universal screening for Methicillin-Resistant Staphylococcus Aureus (MRSA) among patients - Mohammad Noor, Nurul Nadiah; A. Rahman, Nor Azlina; Mohamad Zin, Noraziah; Hanafiah, Alfizah (2015)
Staphylococcus aureus can commonly be found as normal flora in human but the pathogenic strain can lead to health problems. Prompt treatment of patients is important to prevent the spread of infection, especially because it has become resistant to multiple antibiotics including methicillin (thus Methicillin-Resistant Staphylococcus aureus or MRSA) which can lead to higher cost of treatment and increasing mortality. The objective of this research was to evaluate the perceptions of nurses working in high risk wards in Pusat Perubatan Universiti Kebangsaan Malaysia (PPUKM), namely the surgical and orthopaedic wards, regarding the cost-effectiveness and practical issues of universal screening for MRSA on patients admitted to the hospital, as opposed to the screening of only high risk patients as of the current practice. This qualitative study used focus group discussions of the purposely selected nurses as the data collection method. The results show that a majority of the participants agreed for universal screening of MRSA being carried out upon admission of patients, irrespective of the cost. Among others, the reasons given were to prevent the transmission of infection to hospital staff or other healthy individuals and to shorten the length of stay in hospital, which indirectly would be more cost-effective in the long run. Most of them also perceived that cohort isolation would be more cost-effective as compared to individual isolation of MRSA infected patients as a preventive method. All of them had experienced taking swabs from patients for MRSA screening and they thought of it as a simple procedure. In conclusion, majority of the participants perceived that universal screening for MRSA and cohort isolation would be more cost-effective in the prevention of MRSA, besides perceiving no major practical issues if it is going to be carried out in PPUKM.